Exercise Restriction Does Not Change Outcome in Dogs After Diagnosis of Acute Non‐Compressive Nucleus Pulposus Extrusion, Fibrocartilaginous Embolism, or Hydrated Nucleus Pulposus Extrusion - Katherine Phillips; Paul Freeman (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Acute non‐compressive nucleus pulposus extrusion (ANNPE), fibrocartilaginous embolism (FCE), and hydrated nucleus pulposus extrusion (HNPE) all present with acute to peracute onset of myelopathic signs in dogs, for which treatment usually is medical. Conservative management including a period of strict rest usually is recommended because of concern about relapse if immediate exercise is allowed. Hypotheses Allowing exercise after a diagnosis of ANNPE, FCE, or HNPE does not decrease the chance of recovery or predispose to relapse in the short‐term follow‐up period (4 weeks) after discharge. There is no difference in clinical outcome between rested and exercised groups. Animals Forty cases of ANNPE, FCE, or HNPE with follow‐up including at minimum a 4‐week evaluation after discharge. Methods Retrospective study. The exercise group (n = 22) included all dogs the owners of which were not explicitly instructed to rest their dogs, whereas the rest group (n = 18) included all dogs the owners of which were specifically advised to rest their dogs or to restrict their exercise. Results No dogs relapsed or deteriorated between discharge and 4‐week re‐evaluation. No significant difference was found between the rest and exercise groups. Conclusions Allowing exercise after confirming a diagnosis of ANNPE, FCE, or HNPE did not predispose to relapse of clinical signs in the 4 weeks after discharge in our cohort, but the rest group had a higher proportion of HNPE cases, which means interpretation of our findings in this diagnosis must be made with caution.